Regulation of osmC Gene Expression by the Two-Component System rcsB-rcsC in Escherichia coli - Davalos-Garcia, Marcela (American Society for Microbiology, 2001)
The Escherichia coli osmC gene encodes an envelope protein of unknown function whose expression depends on osmotic pressure and growth phase. The gene is transcribed from two overlapping promoters, osmCp(1) and osmCp(2). Several factors regulating these promoters have been reported. The leucine-responsive protein Lrp represses osmCp(1) and activates osmCp(2), the nucleoid-associated protein H-NS represses both promoters, and the stationary-phase sigma factor ς(s) specifically recognizes osmCp(2). This work reports the identification of an additional regulatory element, the two-component system rcsB-rcsC, affecting positively the distal promoter osmCp(1). The response regulator of the system, RcsB, does not affect expression of the proximal promoter osmCp(2). Deletion analysis located the site necessary for RcsB activation just upstream of osmCp(1). In vitro transcription experiments and gel mobility shift assays demonstrated that RcsB stimulates RNA polymerase binding at osmCp(1).